The Role of Nuclear Energy in Achieving Sustainable Energy Solutions - Rajagukguk, Michael; Cornelius Siagian, Ruben; Gunawan, Budi (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: The aim is to assess the role of nuclear energy as a stable and environmentally friendly energy source, as well as its advantages over fossil fuels and renewable energy. The research identifies the benefits, challenges, and technological advances in nuclear energy, as well as the potential for its expanded use in global efforts to reduce carbon emissions and transition to more environmentally friendly energy sources. Study Design/Methodology/Approach: The study used qualitative methodology. Data was collected from secondary sources; scientific papers, government reports, and industry assessments. Findings: Nuclear energy is a stable, low-carbon energy source that is independent of weather conditions, supporting grid stability, especially during times of peak demand or low renewable energy availability. But there are significant challenges. Modern reactor designs and new cooling systems can overcome these challenges and improve nuclear energy efficiency. International co-operation and oversight by the IAEA are essential to ensure global nuclear security. Originality/Value: Comprehensively analyses the role of nuclear energy in meeting global energy needs, combating climate change, and driving technological innovation. Evaluates the benefits and challenges of nuclear energy, with an emphasis on safety, waste management, and technological advancement. Policy recommendations, investment guidelines, and strategies to extend the lifetime of nuclear power plants.